2013
DOI: 10.24095/hpcdp.33.3.06
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cases of congestive heart failure from administrative data: a validation study using primary care patient records

Abstract: Introduction To determine if using a combination of hospital administrative data and ambulatory care physician billings can accurately identify patients with congestive heart failure (CHF), we tested 9 algorithms for identifying individuals with CHF from administrative data. Methods The validation cohort against which the 9 algorithms were tested combined data from a random sample of adult patients from EMRALD, an electronic medical record database of primary care phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
160
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(167 citation statements)
references
References 16 publications
1
160
0
Order By: Relevance
“…Also, the ICES algorithms are not perfect and there is potential for false positives and false negatives in identifying morbidities. However, the validated algorithms for most conditions are generally robust [22][23][24] and with a sample size this large, any minor inaccuracies unless widespread should not be an issue. Also, we do not have an exhaustive list of morbidities, nor does a gold standard presently exist for better measuring multimorbidity with the use of health administrative databases.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the ICES algorithms are not perfect and there is potential for false positives and false negatives in identifying morbidities. However, the validated algorithms for most conditions are generally robust [22][23][24] and with a sample size this large, any minor inaccuracies unless widespread should not be an issue. Also, we do not have an exhaustive list of morbidities, nor does a gold standard presently exist for better measuring multimorbidity with the use of health administrative databases.…”
Section: Discussionmentioning
confidence: 99%
“…Data sources used to define participants, outcomes and covariates included the following: the DAD and the SDS database; the NACRS; the OMHRS; the Ontario Laboratories Information System; the ICES Registered Persons Database demographic and postal year data sets; the OHIP claims database; the Immigration, Refugee and Citizenship Canada Permanent Resident Database; the Ontario Drug Benefit (ODB) Database; and several ICES-derived population-surveillance data sets, including the Chronic Obstructive Pulmonary Disease Database, 26 the Ontario Asthma Database, 27 the Ontario Diabetes Database, 28 the Congestive Heart Failure Database 29 and the Ontario Hypertension Database. 30 These databases are further described in Appendix 1, Supplemental Tables S1 and S2.…”
Section: Methodsmentioning
confidence: 99%
“…The present authors applied validated algorithms (Antoniou, Zagorski, Loutfy, Strike, & Glazier, 2011; Gershon et al., 2009a, 2009b; Hux, Ivis, Flintoft, & Bica, 2002; Schultz, Rothwell, Chen, & Tu, 2013; Tu, Campbell, Chen, Cauch‐Dudek, & McAlister, 2007) to define the proportion of people with a diagnosis of diabetes, hypertension, chronic obstructive pulmonary disease (COPD), asthma, congestive heart failure (CHF) and HIV infection. Based on prior research by project team members, the present authors identified people with a diagnosis in the past two years of any mental disorder, including psychotic disorders and substance‐related disorders, in physician billing (OHIP), hospitalization (Canadian Institute of Health Information [CIHI] Discharge Abstracts Database [DAD], Ontario Mental Health Reporting Systems [OMHRS]) and emergency department (CIHI National Ambulatory Care Reporting System [NACRS]) administrative data (Lunsky et al., 2012).…”
Section: Methodsmentioning
confidence: 99%